Preparation and Characterization of Thermoresponsive In-situ Forming Poloxamer Hydrogel for Controlled Release of Nile red-loaded Solid Lipid Nanoparticles: Controlled release of Nile red loaded SLN by thermoresponsive sol-gel incorporation - Golnar Dorraj; Hamid R. Moghimi (Iranian Journal of Pharmaceutical Sciences, 2013)
Preparation and characterization of thermoresponsive in-situ forming poloxamer hydrogel for controlled release of Nile red-loaded solid lipid nanoparticles. Nanoparticles (NPs) are cleared rapidly from systemic circulation and do not provide sustained action in most cases. To solve this problem, this investigation introduces an erodible in-situ forming gel system as potential vehicles for prolonged release of NPs. In this study, Nile red-containing SLNs were prepared by solidification of an oil-in-water microemulsion using stearic acid, surfactants and co-surfactants. SLN particles were then loaded in a Poloxamerthermoresponsive sol-gel matrix. Dialysis membrane and membrane-less diffusion method were used to study release of the fluorescent probe. Erosion test were carried out by gravimetric method and the medium was checked for zeta potential to investigate existence of intact SLNs. Sol-gel transition temperature was determined by stirring method. Release results showed high entrapment of Nile red in lipid matrix of SLN. Therefore, Nile red content in erosion medium was attributed to SLN particles. Zeta potential of SLNs remained unchanged after sol-gel loading (P>0.05). The correlated released amount of Nile red to dissolved gel weight implied erosion could be major mechanism of SLN release. Results also showed that SLN increase erosion rate of Poloxamer gel and its sol-gel transition temperature. The present study show that thermoresponsivePoloxamer gel can be used to control the release of NPs and those intact NPs are released from this system. The prepared formulation can be used for further investigations in vivo.